(untitled) (Revista Argentina de Musicología, 2026)
This study aims to analyze certain aspects of Georges Aperghis’ work to provide an insight into his approach, aesthetics, and compositional technique. Through this investigation, we explore whether Aperghis’ music can be conceived or defined beyond the inseparable relationship between the performer and the composer in the creative process. From this perspective, the study examines key aspects of two of his works: Les Guetteurs de sons (1980) and Récitations (1978). Although these pieces are not the most representative of his catalog, their selection in this study underscores the idea that theatricality lies at the very core of his artistic approach, not merely in the more overtly theatrical aspects of his work. Editorial History Received: March 31, 2025 Accepted: October 20, 2025